PENGARUH SISTEM DOUBLE PEAK PEREBUSAN TERHADAP OIL LOSSES DARI AIR KONDENSAT PADA PEREBUSAN VERTIKAL DILIHAT DARI PERBEDAAN SUMBER BUAH YANG DIOLAH OLEH PKS HAPESONG PTPN 3 - Aisyah, Siti; Mahyunis; Faisal, Busrizal; Firdaus, Khairin (Institut Teknologi Sawit Indonesia (ITSI), 2024)
In the last 10 years, the Palm Oil Mill (PKS) in Indonesia has grown very rapidly. Most of the large names of oil palm plantations have gradually changed throughout Indonesia to oil palm plantations. One of the processes to achieve efficiency in the Palm Oil Mill can be determined in the fruit ripening process. Where the perfection of the ripening process is influenced by the condition of the fruit and the ripening system. One of the problems that need to be faced in the vertical boiling process is the occurrence of losses or also called oil loss in the condensate air. Oil losses can occur due to various factors, including differences in fruit sources processed in the PKS. In this study, a factorial complete randomized planning method will be used which has two factors. The highest losses are in third party fruit/community fruit with a total of 11.04%, and the lowest total losses are in core plantation fruit with a total of 4.8%. The highest oil losses are in third party fruit or community fruit, this is due to the length of time the fruit has been sorted overnight which can cause the fruit to be overripe and also in fruit that is injured by the loader. The results of this analysis show that the double peak system has a significant impact on oil losses to third parties/community members.